PREDICTION AND TREATMENT OF CATASTROPHIC ANTIPHOSPHOLIPID SYNDROME (CAPS): A CRITICAL REVIEW AND CURRENT APPROACHES (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2023)
Catastrophic antiphospholipid syndrome (CAPS) is a rare but the most severe and life-threatening form of antiphospholipid syndrome (APS), characterized by rapidly progressive multi-organ failure due to small vessel thrombosis. Despite advances in understanding its pathogenesis, mortality in CAPS remains unacceptably high, dictating the need for early diagnosis and aggressive therapy. This review systematizes current data on the pathogenesis, clinical manifestations, diagnosis, and treatment of CAPS. Key pathogenetic mechanisms are examined, including the "second hit" theory, the central role of complement activation, endothelial cell dysfunction, and the "thrombotic-inflammatory storm" concept. Classification criteria and the challenges of differential diagnosis with other thrombotic microangiopathies (TTP, HUS, sepsis, HELLP syndrome) are analyzed. Special attention is given to modern therapeutic approaches: from the standard "triple therapy" (anticoagulants, glucocorticoids, plasma exchange/intravenous immunoglobulins) to the use of targeted agents such as rituximab and eculizumab. Prognostic factors and unresolved issues, including the absence of biomarkers for predicting CAPS development in APS patients, are discussed. It is emphasized that success in treating CAPS depends on a high index of clinical suspicion, rapid diagnosis, and a multidisciplinary approach.